a) 2x + 3 / 5 = 2 - x / 3 - x / * 15
3(2x + 3) = 5(2 - x) - 15x
6x + 9 = 10 - 5x - 15x
6x + 9 = 10 - 20x
6x + 20x = 10 - 9
26x = 1 / : 26
x = 1/26
b) x + 1 / 2 - x - 1 / 3 = 1/4 / * 12
6(x + 1) - 4 (x - 1) = 3
6x + 6 - 4x + 4 = 3
2x + 10 = 3
2x =3 - 10
2x = -7 / : 2
x = - 7/2 = - 3 całe i 1/2
c) 4x + 7 / 2 - 5x - 1 / 6 = x + 5 / *6
3(4x + 7) - (5x - 1) = 6x + 30
12x + 21 - 5x + 1 = 6x + 30
7x + 22 = 6x + 30
7x - 6x = 30 - 22
x = 8
d) x + 5 / 4 - 2x + 1 / 8 = 1/2 * (2 - x)
x + 5 / 4 - 2x + 1 / 8 = 1 - 1/2x / * 8
2(x + 5) - (2x + 1) = 8 - 4x
2x + 10 - 2x - 1 = 8 - 4x
9 = 8 - 4x
4x = 8 - 9
4x = -1 / : 4
x = - 1/4